Feeding two levels of alfalfa hay to heifer calves on winter bluestem pasture and a three-year summary - Smith, E.F.; Koch, B.A.; Good, D.L.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This experiment was designed to collect data in regard to the optimum level of alfalfa hay feeding for calves wintered on bluestem pasture. One group of heifers was fed twice as much alfalfa hay as another, but the supplemental total digestible nutrient intake was maintained at about the same level by feeding grain to heifers on the lower level of alfalfa hay. Two previous tests are reported in Circulars 349 and 358.
Keywords: Beef; Alfalfa hay; Bluestem pasture